Ethnobotanical study of medicinal plants in the Adrar Province, Mauritania. (10th January 2020) - Yebouk, Cheikh; Redouan, Fatima Zahrae; Benítez, Guillermo; Bouhbal, Mohamed; Kadiri, Mohamed; Boumediana, Ahmed Ismail; Molero-Mesa, Joaquín; Merzouki, Abderrahmane
Abstract: Ethnopharmacological relevance: Mauritania is a country in which few ethnobotanical studies have been conducted and consequently the ethnomedical data is scarce. Since the geographical region reflects the transition between tropical and Northern Africa, influenced by the Mediterranean floristic region, the traditional knowledge was influenced by several cultures from tropical Africa as well as Arab, Berber and Islamic societies. Aim of the study: This paper aims to explore and compile the diversity of ethnomedical knowledge in one of the regions of Mauritania and to compare the data with similar studies from surrounding territories. Materials and methods: Surveys and interviews were carried out in 11 villages of Adrar province in northern Mauritania. Data were collected through open, semi-structured interviews (with individuals and focus groups). A sample of 120 people aged between 20 and 70 years, including 24 herbalists and 28 traditional healers was included. Results: Ethnomedical data for 68 plant species belonging to 27 families were obtained. They are used to treat 50 health conditions grouped in 14 pathological groups. Remedies for digestive system disorders, skin problems and respiratory ailments were among the most frequent indications. Leaves were the most frequently used plant part and remedies generally used as a powder for the various applications and a total of 2'317 use reports were gathered. About 55% of the reported species were not cited previously in the literature focusing on Mauritania and neighbouring countries. Moreover, only 6 species are also cited by Ibn al-Baytar (13th century CE). Conclusions: This work shows a promising perspective for future studies, shedding light on the richness and the risk for conservation of traditional knowledge of herbal medicine in Mauritania. Graphical abstract: Image 1